The Intention To Blow The Whistle : Testing The Correlation Between Ethical Leadership And Retaliation In The Organization - Ilham Nuryana Fatchan; Alfalisyado Alfalisyado; Irawan Randikaparsa; Fuad Hudaya Fatchan (Integrated Journal of Business and Economics, 2024)
This research helps explain the factors that influence a person's intention to do whistleblowing. This study examines the effect of retaliation (the treatment of revenge) and ethical leadership on the whistleblowing decisions of postgraduate students with masters of accounting at universities in Central Java. The novelty of our study is First, we fill in gaps in previous studies using students as the population; most studies use employees (such as auditors) as the main population.